Anéis de grupos inteiros de grupos de Frobenius - Cardoso, Nefran Sousa (2002)
This dissertation is divided into two chapters. The first chapter introduces the Group Rings, the Frobenius Groups and their properties. In the beginning of the second chapter are presented Conjectures of Zassenhaus . The weaker version of these conjectures is demonstrated for Amitsur Groups. At the end of the second chapter, the validity of that version is proven to Frobenius Groups. Such Frobenius Groups are those whose complement, checks the validity of this conjecture. In the final part we present the Hall subgroups and Schur-Zassenhaus Theorem.